O tema no processo criativo da Asmarias Companhia de Teatro - Lima, Hélio Júnior Rocha de (2011)
Seted in the context of the educational actions of Casa Renascer, a non-governmental organization, located in Natal city, which had as its primary purpose the care with children and adolescent girls in vulnerable situations, this research is based on describing and analysis on the topic in the creative process developed by Asmarias Theatre Company from 1993 to 2003, a process that culminated in the assembly of the dramatic text, Mateus e Mateusa, of Qorpo-Santo. In this research is focused on the route of the Theatre Company has done so much theater in its early history (1993), with the practice of reading and dramatic writing in the preparation of didactic material called Primer of Inventions, as in the procedures with theater street and forum theater (1997 to 2000) to the reunion in 2001 of seven teenagers which articulated the last group formation next to the assembly's text Qorpo-Santo (2002- 2003). During the development on this learning, the evolution of the creative process based on institutional theme when asked if one can provide moments of educational experiences through the traditional form of theater, with reference to the issues inherent in the dramatic texts considered classics. The debate on the issue through research and analysis in its descriptions and finds in the interim between his past and present indications that lead to conclusive guises. The methodology, which is guided by research, is based in theatrical archeology (PAVIS, 2005), the evidential paradigm (GINZBURG, 1989) and the second approaches the experiences narrated by Benjamin (1985). We selected documents in formats of written texts, photographic and filmed, and identified in these files, marks and tracks which took us to understand the subject in the creative process of Asmarias Theatre Company during the tests with the dramatic text, Mateus and Mateusa, of Qorpo-Santo. In this theatrical practice, located in the field of the theater pedagogy, it appears that the actions across thematic theater in the Casa Renascer and allowed the formation of critical aesthetic perspective and personal social dimension of the subjects involved. The theme has gained a significant proportion in the theatrical activity as a guiding point of the creative process of Theatre Company, taking in the theatrical art form. In this sense, the creative process with the dramatic and classic texts won the educational dimension to address the issue in the movement of the drama as the focus of individual creation which added to the collective universe of the interactive game